Solid-state reaction silicon nanocrystals in sol-gel tetraethylorthosilicate thin films - Lau, Hon Wu (2008)
Silicon nanocrystals (Si nc) have exhibited its potential in light emission and memory effects for the past decade. Due to its compatibility with Si technology and materials, this form of nanostructure is highly valued by many research groups. Many methods have been proposed to fabricate Si nc which includes ion-implantation, chemical vapour deposition (CVD), laser ablation and co-sputtering. However, these methods are often expensive and require a matrix, such as SiO2 or Si3N4, to embed the Si nc. The presence of such a matrix creates complications for the study of the Si nc intrinsic characteristics. In seeking a method to eliminate these two constraints, solid state reaction (SSR) - a dry chemical or physical process without adding any solvent - (also known as mechanical milling in this case) is employed to fabricate Si nc in this project.